Energy storage applications of CdMoO₄ microspheres - Isacfranklin, M. (2022)
In this study, a one-step hydrothermal method was used to synthesize cadmium molybdenum oxide and revealed cationic cetyltrimethylammonium bromide surfactant effects on material preparation and energy storage characteristics. X-ray diffraction confirmed tetragonal-phase CdMoO4. Symmetric stretching modes of molybdenum oxide were confirmed from a Raman spectrum. A Fourier-transform infrared spectrum confirmed the presence of functional groups. Scanning electron microscopy images revealed a bunch of hierarchical microspheres of about 100–200 nm diameter. The specific capacitance achieved for CdMoO4, 0.1 M CTAB + CdMoO4, and 0.2 M CTAB + CdMoO4 were 200 F/g, 310 F/g, and 382 F/g, respectively, at 0.5 A/g. In addition, long-term cyclic stability for the best performing electrode (0.2 M CTAB + CdMoO4) material was investigated to explore cyclic performances of the supercapacitor. During the experiment, 86.01% capacity was retained after 5000 cycles at 5 A/g. The product activity is promising for high-efficiency supercapacitors due to the ease of production, environmentally friendly nature, and low cost of the synthesized material.